2011
DOI: 10.1002/macp.201100197
|View full text |Cite
|
Sign up to set email alerts
|

Dextran‐Based Polycations: Thermodynamic Interaction with Water as Compared With Unsubstituted Dextran, 2 – Flory/Huggins Interaction Parameter

Abstract: The Flory‐Huggins interaction parameter χ is determined as a function of volume fraction of polymer φ by vapor‐pressure measurements at 25, 37.5 and 50 °C for five dextran samples that differ in f, the fraction of randomly distributed charged monomer units. The function χ(φ) has a minimum that is shifted towards lower χ values as f increases. The higher the temperature, the more the individual curves fan out. The heats of dilution at high polymer concentrations change from exothermal to endothermal as f increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 14 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…We have observed that it required a longer time (∼14 days) for the PAA-EICP solution to completely dry compared with pure EICP solutions . Vapor pressure measurement showed that adding PAA into DI water could significantly lower the evaporation rate (Figure S2a). The interactions between PAA and water molecules were energetically favorable, which was attributed to the carboxyl rich, super hydrophilic structure of PAA (Figure S2b).…”
Section: Resultsmentioning
confidence: 98%
“…We have observed that it required a longer time (∼14 days) for the PAA-EICP solution to completely dry compared with pure EICP solutions . Vapor pressure measurement showed that adding PAA into DI water could significantly lower the evaporation rate (Figure S2a). The interactions between PAA and water molecules were energetically favorable, which was attributed to the carboxyl rich, super hydrophilic structure of PAA (Figure S2b).…”
Section: Resultsmentioning
confidence: 98%
“…The derived interaction parameters are χ = 0.47 for D 2 O and χ = 0.05 ± 0.04 for DD-DES, suggesting that although both act as good solvents for PVP, water is closer to a Θ solvent (χ = 0.5) solvent whereas DES approaches the ideal solution limit (i.e., where there are no net effective interactions, χ = 0). The fact that χ is lower for DES, whereas the solubility limit of PVP in DES is also lower, might suggest a concentration dependence of the interaction parameter, which we do not consider here.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[74][75][76][77] This indicates that the limited set of fundamental parameters used in regular solution theory may be insufficient when the solution mixing properties change with concentration, which may prove crucial to making more quantitative predictions. Accounting for concentration-dependent interaction parameters is somewhat analogous to considering MFC parameters that are different in the bulk and the surface domain, thereby establishing different mixing properties in the two domains.…”
Section: Comparing Theory With Protein Folding Experimentsmentioning
confidence: 96%